RSV-related hospitalization and outpatient palivizumab use in very preterm (born at <29 wGA) infants: 2003-2020. Issue 6 (30th November 2022) - Packnett, Elizabeth R.; Winer, Isabelle H.; Larkin, Heather; Oladapo, Abiola; Gonzales, Tara; Wojdyla, Matthew; Goldstein, Mitchell; Smith, Vincent C.
ABSTRACT: Respiratory syncytial virus (RSV) is a leading cause of bronchiolitis and pneumonia in children under one year and a leading cause of infant hospitalization. Palivizumab was approved by the FDA in 1998 as RSV immunoprophylaxis to prevent severe RSV disease in children with specific health conditions and those born at <35 weeks gestational age (wGA). This study compared RSV-related hospitalization (RSVH) and RSVH characteristics in very preterm (<29 wGA) and term (>37 wGA) infants. Using the MarketScan Commercial and Multi-State Medicaid administrative claims databases, infants born between 7/1/2003 and 6/30/2020 were identified and classified as very preterm or term. Infants with evidence of health conditions, such as congenital heart disease and cystic fibrosis, were excluded. During 2003–2020 RSV seasons (November to March), claims incurred by infants while they were <12 months old were evaluated for outpatient administration of palivizumab and RSVH. The study included 40, 123 very preterm infants and 4, 421, 942 term infants. Rate of RSVH in very preterm infants ranged 1.5–3.8 per 100 infant-seasons in commercially insured infants and 3.5–8.4 in Medicaid insured infants and were inversely related to wGA at birth. Relative risk of RSVH in very preterm was 3–4 times higher, and ICU admissions and mechanical ventilation were more common during RSVH in very preterm infants relative to term infants. However, these outcomes were less common or less severe in very preterm infants who received outpatient palivizumab administration, despite evidence of higher baseline risk of RSVH in these infants.